Improving Students’ Learning Motivation through Active Learning Methods in Islamic Religious Education Learning ror Fourth Grade Students at Sd N 104 Bengkulu City - Amiliana, Shonia; Simanjuntak, Sya'aba Oktavia; Salamah, Salamah; Ediansyah, Ediansyah (International Journal on Advanced Science, Education, and Religion, 2025)
This study aims to improve students’ learning motivation through the implementation of active learning methods in Islamic Religious Education (PAI) for fourth-grade students at SDN 104 Bengkulu City. The background of this research is based on the low level of students’ motivation, which can be seen from their lack of active participation, interest, and involvement in the learning process. The method used in this study is Classroom Action Research (CAR) with both qualitative and quantitative approaches, carried out in two cycles. Each cycle consists of planning, implementation, observation, and reflection stages. Data were collected through observation, interviews, and documentation, while the data analysis used a descriptive technique. The results show that the application of active learning methods can significantly improve students’ learning motivation. This can be seen from the increase in students’ participation during lessons, their confidence in asking and answering questions, as well as the improvement in learning outcomes in each cycle. Therefore, active learning methods are proven to be effective in improving students’ motivation in Islamic Religious Education (PAI) for fourth-grade students at SDN 104 Bengkulu City.